Effect of tooth preparation design on marginal adaptation of composite resin CAD-CAM onlays - Yang, Yang; Yang, Zhen; Zhou, Jianfeng; Chen, Li; Tan, Jianguo (The Journal of prosthetic dentistry, 2020)
Although different preparation designs have been proposed for onlays fabricated by computer-aided design and computer-aided manufacturing (CAD-CAM), their effect on marginal adaptation is unclear. The purpose of this in vitro study was to investigate the effect of tooth preparation designs on the marginal and internal adaptation of ceramic-reinforced composite resin CAD-CAM onlays. A traditional preparation with a heavy chamfer on the functional cusp and a contrabevel on the nonfunctional cusp and a shoulder preparation with equal reduction on all cusps were used for mesial-occlusal-distal (MOD) onlay preparations. Ceramic-reinforced composite resin onlays were designed and milled based on the scanned prepared teeth. A digital silicone replica technique was used to determine marginal discrepancies between preparations and onlay restorations. A total of 100 numeric distances (representations of the fit in each region) were measured in 3 distinct regions: the buccal margin, lingual margin, and internal area. Independent Student t tests were used to determine significant differences (α=.05). Traditional preparation designs resulted in significantly smaller overall discrepancies (50.9 ±0.5 μm and 139.1 ±5.4 μm, P<.001) and smaller marginal discrepancies in the buccal (49.7 ±1.4 μm and 135.8 ±2.2 μm, P<.001) and lingual areas (47.1 ±1.0 μm and 133.4 ±1.1 μm, P<.001). The marginal adaptation of ceramic-reinforced composite resin CAD-CAM onlays was affected by the preparation design. The traditional preparation design offered better marginal adaptation; therefore, it is recommended in clinical practice.